2022
DOI: 10.3390/cancers14112790
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of MFG-E8 Confer a Good Prognosis in Prostate and Renal Cancer Patients

Abstract: Milk fat globule-epidermal growth factor-8 (MFG-E8) is a glycoprotein secreted by different cell types, including apoptotic cells and activated macrophages. MFG-E8 is highly expressed in a variety of cancers and is classically associated with tumor growth and poor patient prognosis through reprogramming of macrophages into the pro-tumoral/pro-angiogenic M2 phenotype. To date, correlations between levels of MFG-E8 and patient survival in prostate and renal cancers remain unclear. Here, we quantified MFG-E8 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 50 publications
(80 reference statements)
0
1
0
Order By: Relevance
“…This may be due to genetic changes in the tumor microenvironment that are initiated by cancer cells or immune helper cells during tumor progression, with macrophages exhibiting predominantly M2-type polarization; It exhibits an immunosuppressive tumor phenotype and promotes tumor progression, metastasis, and treatment resistance. MFG-E8 expression has been found to be associated with M2 polarization in a variety of cancers, including the oral cavity, prostate, and melanoma [ 25 ]. In our study, we found that MFG-E8 can promote the transformation of macrophages from GC patients to M2.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to genetic changes in the tumor microenvironment that are initiated by cancer cells or immune helper cells during tumor progression, with macrophages exhibiting predominantly M2-type polarization; It exhibits an immunosuppressive tumor phenotype and promotes tumor progression, metastasis, and treatment resistance. MFG-E8 expression has been found to be associated with M2 polarization in a variety of cancers, including the oral cavity, prostate, and melanoma [ 25 ]. In our study, we found that MFG-E8 can promote the transformation of macrophages from GC patients to M2.…”
Section: Discussionmentioning
confidence: 99%